End of an era? Forty years of Dorem Afrike and Yiddish Kultur in South Africa - Ginsberg, C. J. (Journal for semitics, 2011)
This article looks at the journal published in Yiddish in Johannesburg, South Africa from 1948 until 1991, against the backdrop of the publication of earlier periodicals in that language. In the early years of publication, newspapers seemed to fare better than cultural journals, although both struggled to establish themselves. Initially, the cultural journals rarely survived for longer than a few years at most. The later journal, Dorem Afrike (1948+) achieved longevity, and the present article attempts to gain an insight into why this should have been the case in the post-Holocaust period. Factors such as secular culture and political ideologies are examined. The editors of Dorem Afrike published evaluatory articles every five years, during the course of its existence. In order to gain insight into how the journal viewed itself, it was decided to focus on the anniversary issues published every five years (5th, 10th anniversary and so on). In general terms, the main body of the article is divided into sub-headings according to these intervals. The essays published at these intervals are studied in an attempt to gain an understanding of how the journal saw itself as it developed. From time to time articles of assessment from outside the Kultur Federatzye were published - these are also consulted in this article in the hope that they might provide an added perspective.